CONCEPT OF CHEMOTHERAPY. THE ROLE OF CHEMOTHERAPY IN MODERN MEDICINE - Shukurova Shoxina Tuyg’unovna; Ochilova Dilshoda Otabekovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, the concept of chemotherapy, its origin and its place in modern medicine are widely covered. The article provides detailed information about the role of chemotherapy in the treatment of cancer, the drugs used, their mechanism of action, and side effects affecting the patient’s body. Based on modern researches, the efficiency of chemotherapy methods and future development prospects are also analyzed. The article is intended for medical professionals, students and a wide audience interested in healthcare.